Flavonoids as anti-inflammatory agents - Serafini, Mauro; Peluso, Ilaria; Raguzzini, Anna (Proceedings of the Nutrition Society, 2010)
Epidemiological evidence suggests that a high intake of plant foods is associated with lower risk of chronic diseases. However, the mechanism of action and the components involved in this effect have not been identified clearly. In recent years, the scientific community has agreed to focus its attention on a class of secondary metabolites extensively present in a wide range of plant foods: the flavonoids, suggested as having different biological roles. The anti-inflammatory actions of flavonoids in vitro or in cellular models involve the inhibition of the synthesis and activities of different pro-inflammatory mediators such as eicosanoids, cytokines, adhesion molecules and C-reactive protein. Molecular activities of flavonoids include inhibition of transcription factors such as NF-κB and activating protein-1 (AP-1), as well as activation of nuclear factor-erythroid 2-related factor 2 (Nrf2). However, the in vitro evidence might be somehow of limited impact due to the non-physiological concentrations utilized and to the fact that in vivo flavonoids are extensively metabolized to molecules with different chemical structures and activities compared with the ones originally present in the food. Human studies investigating the effect of flavonoids on markers of inflammation are insufficient, and are mainly focused on flavonoid-rich foods but not on pure molecules. Most of the studies lack assessment of flavonoid absorption or fail to associate an effect on inflammation with a change in circulating levels of flavonoids. Human trials with appropriate placebo and pure flavonoid molecules are needed to clarify if flavonoids represent ancillary ingredients or key molecules involved in the anti-inflammatory properties of plant foods.